Debt overhang, rollover risk, and corporate investment: Evidence from the European crisis - Sebnem Kalemli-Ozcan; Luc Laeven; David Moreno (European Central Bank (ECB), 2019)
We quantify the role of financial factors behind the sluggish post-crisis performance of European firms. We use a firm-bank-sovereign matched database to identify separate roles for firm and bank balance sheet weaknesses arising from changes in sovereign risk and aggregate demand conditions. We find that firms with higher debt levels and a higher share of short-term debt reduce their investment more after the crisis. This negative effect is stronger for firms linked to weak banks with exposures to sovereign risk, signifying increased rollover risk. These financial channels explain about 60% of the decline in aggregate corporate investment.
Keywords: E22; E32; E44; F34; F36; G32; 330; Firm Investment; Debt Maturity; Rollover Risk; Bank-Sovereign Nexus; Finanzkrise; Unternehmensfinanzierung; Verbindlichkeiten; Investition; Investitionsrisiko; EU-Staaten